DISPLAYS OF THE SENSE OF THE HUMOUR IN PSYCHOLOGICAL DEFENCE SYSTEM - Irina Strazdiņa (European Scientific Journal, ESJ, 2015)
The paper studies the specific features of humour, its displays, as well as a psychological protection as functioning of a defined psycho hygienic factor for improvement of self-feeling, as a personality‘s stabilization system. Adaptive human behaviour is described. Four humour styles – affiliative, self-enhancing, aggressive and disparaging, self-defeating style of humour – are updated.